Physics - Green, Dan, 1975 June 20-; Basher, Simon (Boston : Kingfisher, 2008)
The authors mix science and art together in order to explain the basic concepts of physics including the interaction of energy and matter.
E(instein)=mc2 -- Old school -- Hot stuff -- Wave gang -- Light crew -- Atom family -- Nuclear heavies -- Electric cuties.
Cover title: Physics :.
Includes index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
School Library Journal, August 2008.
Keywords: Physics -- Juvenile literature; Physics; Physics